2022
DOI: 10.1126/sciadv.abk3234
|View full text |Cite
|
Sign up to set email alerts
|

Ultrarapid lytic granule release from CTLs activates Ca 2+ -dependent synaptic resistance pathways in melanoma cells

Abstract: Human cytotoxic T lymphocytes (CTLs) exhibit ultrarapid lytic granule secretion, but whether melanoma cells mobilize defense mechanisms with commensurate rapidity remains unknown. We used single-cell time-lapse microscopy to offer high spatiotemporal resolution analyses of subcellular events in melanoma cells upon CTL attack. Target cell perforation initiated an intracellular Ca 2+ wave that propagated outward from the synapse within milliseconds and triggered lysosomal mobilization to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(36 citation statements)
references
References 486 publications
(656 reference statements)
4
32
0
Order By: Relevance
“…While the process of MTOC repolarization and granule convergence towards synapse has been shown to be very rapid, monitoring Ca 2+ entry into target cells at high time resolution as a marker of plasma membrane perforation provided the surprising result that lytic granule secretion can start even earlier than MTOC re-positioning at the LS. Pore formation-dependent Ca 2+ entry into target cells was indeed detected as early as 30-40 seconds after human CTL contact with target cells in many conjugates ( 57 , 58 ), while other studies on human NK cells have shown perforation of the target cell membrane (as detected by propidium iodide penetration) within a similar time frame ( 59 ). These results are intriguing as they imply that the entire process of lethal hit delivery comprising TCR-coupled signal transduction, Ca 2+ -dependent lytic granule secretion, and perforin-mediated pore formation can occur within seconds, making CTL-mediated cytotoxicity an extraordinarily rapid biological phenomenon.…”
Section: Choreography and Outcome Of Ctl/target Cell Dynamic Encountersmentioning
confidence: 85%
See 3 more Smart Citations
“…While the process of MTOC repolarization and granule convergence towards synapse has been shown to be very rapid, monitoring Ca 2+ entry into target cells at high time resolution as a marker of plasma membrane perforation provided the surprising result that lytic granule secretion can start even earlier than MTOC re-positioning at the LS. Pore formation-dependent Ca 2+ entry into target cells was indeed detected as early as 30-40 seconds after human CTL contact with target cells in many conjugates ( 57 , 58 ), while other studies on human NK cells have shown perforation of the target cell membrane (as detected by propidium iodide penetration) within a similar time frame ( 59 ). These results are intriguing as they imply that the entire process of lethal hit delivery comprising TCR-coupled signal transduction, Ca 2+ -dependent lytic granule secretion, and perforin-mediated pore formation can occur within seconds, making CTL-mediated cytotoxicity an extraordinarily rapid biological phenomenon.…”
Section: Choreography and Outcome Of Ctl/target Cell Dynamic Encountersmentioning
confidence: 85%
“…It is conceivable that microtubules (MT)-initiation sites ( 62 ) might be formed at the IS during the first seconds following productive TCR engagement, leading to microtubule nucleation at the synaptic area and docking of few nearby lytic granules. As will be discussed in the following sections, while ultra-rapid lytic granule secretion confers flexibility and efficacy to the CTL killing behavior, this rapid exocytosis might also be detrimental for killing efficacy under some circumstances ( 57 ).…”
Section: Choreography and Outcome Of Ctl/target Cell Dynamic Encountersmentioning
confidence: 99%
See 2 more Smart Citations
“…While likely not being directly toxic, perforin pore-dependent Ca 2+ elevation occurs in 50% of all CTL-melanoma cell interactions and in 90% of eventually lethal events [13]. In human melanoma cells, the Ca 2+ influx triggers lysosome accumulation and, likely, membrane insertion at the immune synapse and resealing of the perforin-mediated membrane defects, which increases melanoma resistance to CTL-induced killing [25,26]. Plasma membrane defects are repaired, within minutes, by internalization or shedding of the damaged site, by the endosomal sorting complex required for transport [ESCRT(III)] machinery, Rab 27 and annexin A7 [27].…”
Section: Plasma Membrane Damagementioning
confidence: 99%